1998
DOI: 10.1177/107424849800300407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin on Collagen Glycation and Diastolic Dysfunction in Diabetic Myocardium

Abstract: BACKGROUND: Collagen accumulation in the myocardial interstitium of diabetic animals is considered to promote diastolic stiffness through advanced glycosylation. Because in vitro data suggest that metformin can modify glycosylation, this study was undertaken in a canine diabetic model 4 months in duration. METHODS AND RESULTS: Untreated diabetics (group II) and diabetics treated with metformin alone (group III) or with insulin (group IV) were compared in the basal state and during volume infusion. Basal hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…A previous animal study demonstrated that metformin provided cardio-protection against hyperglycaemia-induced abnormalities in myocyte relaxation [31], possibly due to its effect on insulin resistance, which may prevent the increment of diastolic chamber stiffness but have no effect on elevated collagen concentration in diabetes [32]. However, other studies have shown that metformin treatment did not increase glucose oxidation or glucose disposal under conditions of physiological hyperinsulinaemia [33] and even had no significant effect on insulin sensitivity [34].…”
Section: Discussionmentioning
confidence: 99%
“…A previous animal study demonstrated that metformin provided cardio-protection against hyperglycaemia-induced abnormalities in myocyte relaxation [31], possibly due to its effect on insulin resistance, which may prevent the increment of diastolic chamber stiffness but have no effect on elevated collagen concentration in diabetes [32]. However, other studies have shown that metformin treatment did not increase glucose oxidation or glucose disposal under conditions of physiological hyperinsulinaemia [33] and even had no significant effect on insulin sensitivity [34].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal studies have shown that metformin is able to react strongly with decarbonyl compounds and could thus decrease AGE formation [137]. Whether and how the risk can be lowered more considerably and consistently by lowering the meal-related glucose excursions has yet to be determined.…”
Section: Biochemical and Physiological Responses To Mealmentioning
confidence: 99%
“…For example, one experimental study of diabetic mice demonstrated that chronic use of metformin prevented the formation of collagen-linked advanced glycosylation end products, and another study found that administration of metformin inhibited cardiac fibrosis induced by pressure overload in nondiabetic mice (31,32).…”
Section: Cardiac Fibrosismentioning
confidence: 99%